2009
DOI: 10.1007/s00125-009-1263-5
|View full text |Cite
|
Sign up to set email alerts
|

Levels of soluble receptor for AGE are cross-sectionally associated with cardiovascular disease in type 1 diabetes, and this association is partially mediated by endothelial and renal dysfunction and by low-grade inflammation: the EURODIAB Prospective Complications Study

Abstract: Aims/hypothesis Plasma soluble receptor for AGE (sRAGE) may reflect the activity of the AGE-RAGE axis, which has been proposed as a potential mechanism linking hyperglycaemia to vascular complications in diabetes. We have therefore investigated: (1) whether sRAGE is associated with greater prevalence of cardiovascular disease (CVD) and microvascular complications in type 1 diabetic individuals; and (2) the extent to which any such associations are explained by markers of endothelial and renal dysfunction and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
44
2
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 51 publications
9
44
2
4
Order By: Relevance
“…There are additional controversial results regarding sRAGE levels in atherosclerosis. Nin et al 34 showed in a cross-sectional study that sRAGE levels are higher in type 1 diabetic patients with CV diseases than in those without the disease; Humpert et al 5 demonstrated a positive association between sRAGE and urinary albumin excretion in 90 patients with type 2 diabetess.…”
Section: Discussionmentioning
confidence: 99%
“…There are additional controversial results regarding sRAGE levels in atherosclerosis. Nin et al 34 showed in a cross-sectional study that sRAGE levels are higher in type 1 diabetic patients with CV diseases than in those without the disease; Humpert et al 5 demonstrated a positive association between sRAGE and urinary albumin excretion in 90 patients with type 2 diabetess.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma levels of C-reactive protein (CRP) were measured by a highly sensitive in-house ELISA, and plasma levels of interleukin 6 (IL6) and tumour necrosis factor a (TNFa) were measured using commercially available ELISA kits (R&D Systems). The intra-and inter-assay CV for CRP, IL6 and TNFa were 3.9 and 8.7%, 4.5 and 9.0%, and 7.3 and 8.5% respectively (2,26).…”
Section: Biomarkersmentioning
confidence: 92%
“…Soluble vascular cell adhesion molecule-1 (sVCAM-1) and soluble E-selectin (sE-selectin) were measured in duplicate by sandwich enzyme immunoassays (R&D Systems, Oxon, UK). The intra-and inter-assay CV for sVCAM-1 were 4.0 and 9.1%, respectively, and for sE-selectin were 2.1 and 3.1% respectively (2,26).…”
Section: Biomarkersmentioning
confidence: 93%
See 2 more Smart Citations